2020
DOI: 10.14716/ijtech.v11i1.3213
|View full text |Cite
|
Sign up to set email alerts
|

Quality Analysis of Chili Treated with Aqueous Ozone Treatment and Improved Transportation and Handling Technology

Abstract: The objective of this research is to study the reduction of chili postharvest losses (PHL) after implementation of aqueous ozone treatment, perforated packaging and refrigerated transportation in inter-city distribution. The completely randomized design method was used in the research, with five levels of combination treatments of chili: (i) aqueous ozone treatment; refrigerated transportation; (ii) no ozone treatment; refrigerated transportation; (iii) aqueous ozone treatment; non-refrigerated transportation;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Quantity loss was reduced from 2.16% to 1.82% and quality loss from 6.70% to 1.68%. Moreover, the colour and texture (hardness) of the chili was maintained, showing a preserved freshness, which is an important parameter in chili marketing [7].…”
Section: Postharvest Handling Technologymentioning
confidence: 97%
See 1 more Smart Citation
“…Quantity loss was reduced from 2.16% to 1.82% and quality loss from 6.70% to 1.68%. Moreover, the colour and texture (hardness) of the chili was maintained, showing a preserved freshness, which is an important parameter in chili marketing [7].…”
Section: Postharvest Handling Technologymentioning
confidence: 97%
“…Depending on the type of technology component chosen, the level of post-harvest loss is different. Table2shows the value of chili loss due to the application of different technology components[7].…”
mentioning
confidence: 99%
“…Water loss in products significantly reduced during storage that might be caused by ozone treatment. Ozone treatment can inhibit the turgor pressure of chili and maintain firmness [23].…”
Section: Water Lossmentioning
confidence: 99%
“…This research did not analyze the relationship between color and customer acceptance. However, previous research on chilies have shown that the initial color (degree of redness) and physiological activity of chili might influence chili color, which is essential quality criterion for evaluating customer approval (Munarso et al, 2020). According to a prior research, customers prefer the color of chili that has been kept cold at 10℃ for 8 and 14 days over chili that has been stored at room temperature (Asgar et al, 2015).…”
Section: Table 1 Physical Properties Of Fresh Red Chilies During Storagementioning
confidence: 99%